PELATIHAN PEMBUATAN ABON IKAN LELE KEPADA IBU-IBU PKK DAN MASYARAKAT DI LINGKUNGAN PTPN III GUNUNG PAMELA SUMATERA UTARA - Miranti Miranti; Mahyu Danil; Muhammad Nuh; Wan Bahroni Jiwar Barus; Susan Novrini (Jurnal Pengabdian Mitra Masyarakat, 2022)
Shredded catfish is an instant, fast and practical food that uses catfish meat as the main raw material which is added with spices and then fried. Shredded catfish product is an alternative to extend the shelf life and increase its economic value. In the PTPN III Gunung Pamela, North Sumatra environment, many people in PTPN III Gunung Pamela have catfish ponds, so it is possible to empower the surrounding community to become Usaha Mikro Kecil dan Menengah (UMKM) so that they can improve the community's economy. The shredded catfish product has its own advantages compared to other shredded fish, namely it has high nutrients, especially protein, while the cholesterol level is low, besides that it also contains leucine and lysine.